2020
DOI: 10.32674/jis.v10i2.765
|View full text |Cite
|
Sign up to set email alerts
|

How Do Chinese International Students View Seeking Mental Health Services?

Abstract: This study explored how Chinese international students view seeking mental health services. One hundred and ten Chinese international students responded to the Attitude Toward Seeking Professional Psychological Help Scale–Short Form (ATSPPH-SF) and a demographic questionnaire. Results of our data analysis revealed no significant main effects of the demographic factors (gender, length of stay in the United States, and awareness of on-campus counseling services) on attitudes toward seeking mental health services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
(70 reference statements)
0
22
0
1
Order By: Relevance
“…First, there was a stronger emphasis on a group of students or study destination. For example, in recent years, the research on international students’ mental health showed a strong focus on the Chinese [ 80 , 81 , 82 , 83 ], Japanese [ 84 , 85 ], and medical international students [ 86 , 87 , 88 ]. Meanwhile, Australia has received more attention as a study destination [ 83 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, there was a stronger emphasis on a group of students or study destination. For example, in recent years, the research on international students’ mental health showed a strong focus on the Chinese [ 80 , 81 , 82 , 83 ], Japanese [ 84 , 85 ], and medical international students [ 86 , 87 , 88 ]. Meanwhile, Australia has received more attention as a study destination [ 83 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that international students are less likely to seek help and use university resources. For example, numerous students reported not using the counseling center on their campus and many others were not even aware of counseling services available to them (Chen et al, 2020). Willis-O'Connor (2014) identified factors that contribute to the underutilization of campus-based counseling services by international students, with culture highlighted as one of the key factors in help-seeking behavior.…”
Section: Help-seeking Behaviorsmentioning
confidence: 99%
“…Motivation to sustain the life of the Pandemic by pursuing a business model transformation with the support of digital technology [11] For teachers, lecturers and students, of course, the skills to apply technology are of minimum importance to be able to access their respective tasks, or if you want more skills, they can be used as a medium for business in the midst of a pandemic. However, when there are problems that arise, services are still needed, especially the increased stress during a pandemic students need mental health services [12] and very necessary.…”
Section: Literature Reviewmentioning
confidence: 99%